A Review of Dietary Influences on Cardiovascular Health: Part 2: Dietary Patterns - Stradling, Clare; Hamid, Mash; Taheri, Shahrad; Neil Thomas, G. (Cardiovascular & Haematological Disorders - Drug Targets, 2014)
Dietary recommendations are key to cardiovascular disease (CVD) management. The underpinning evidence is generally based on data generated from single nutrient or food types. However, food is not consumed in such a manner, and components may interact synergistically or antagonistically depending on the dietary composition. Analyses of dietary patterns have attempted to address these important issues. The aim of this review is to present the current evidence on three major dietary patterns and their relationship with CVD. The most widely reported is the Mediterranean diet, which is characterised by abundant use of olive oil, and plant-based foods, moderate consumption of fish, dairy products, alcohol with meals, and a relatively low intake of red meat. The strongest evidence of causality has been established for the Mediterranean diet and unlike other dietary patterns has been shown to significantly reduce major CVD events. The Dietary Approach to Stop Hypertension (DASH), emphasising fruit, vegetables and low fat dairy products, has successfully been shown to lower blood pressure and cholesterol levels. However, its true effects on CVD under freeliving conditions have yet to be fully explored. The available evidence is encouraging for CVD prevention, but long-term effectiveness is unclear. Very low-carbohydrate diets appear to exert their favourable effect on CVD risk factors via weight loss. However, longterm effectiveness and safety remains unclear. The available evidence supports the role of the DASH and Mediterranean diets in the prevention of CVD.
Keywords: mediterranean diet